PENGARUH CASH TURNOVER, RECEIVABLE TURNOVER DAN INVENTORY TURNOVER TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (Periode 2009 - 2017) - Siti Maulida, Siti Maulida; Sigit Mulyanto, Sigit Mulyanto (Fakultas Ekonomi Universitas 45 Surabaya, 2019)
The purpose of this research is to determine the effect of Cash Turnover, receivable turnover and inventory turnover to profitability in manufacturing companies on the Indonesia Stock Exchange in the period 2009 to 2017. This research uses a multiple regression analysis model. This result of this research showed that there was no effect between Cash Turnover on profitability, while the receivable turnover and inventory turnover variables have a positive effect on profitability.